Output feedback control design using Extended High-Gain Observers and dynamic inversion with projection for a small scaled helicopter. (November 2021) - Lee, Joonho; Seo, Joohwan; Choi, Jongeun
Abstract: This paper presents the output feedback control design for a tracking problem of a small-scale helicopter in the presence of uncertainties. The dynamics of the helicopter is an underactuated mechanical system and the form of control inputs is nonaffine. A time-scale approach is suggested to cope with underactuated mechanical systems to overcome lack of the number of inputs. A newly developed dynamic inversion with projection is used to deal with nonaffine control inputs to increase the region of attraction as compared to linearized inputs, i.e., an affine control input form and to deal with actuator's constraints and peaking in estimates from an Extended High-Gain Observer. The Extended High-Gain Observer is employed to quickly estimate model uncertainties and external disturbances. The singular perturbation method is used to analyze the stability of the closed-loop system in a multi-time scale structure. Based on the stability analysis, the design procedure for the proposed algorithm is presented for practical implementation. The effectiveness of the proposed control algorithm is shown via numerical simulations as well as experimental tests with a small-scale helicopter in an outdoor environment.